INTERAKSI GURU DAN SISWA DALAM PEMBELAJARAN BERBASIS DISKUSI: ANALISIS KONSTRUKTIVISME SOSIAL Studi Kasus di SMP Negeri 52 Kabupaten Seram Bagian Timur, Provinsi Maluku - Adiati Tomia; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher-student interactions in discussion-based learning using a social constructivism perspective at SMP Negeri 52, East Seram Regency, Maluku Province. The research employed a qualitative descriptive approach with a case study method. Data were collected through classroom observations conducted in two meetings, teacher interviews, and learning documentation. The findings revealed that discussion-based learning was able to increase students’ engagement in the learning process through group collaboration, social communication, and active participation in exchanging ideas. Teachers played a role as facilitators by providing scaffolding through guidance, motivation, and assistance during classroom discussions. However, several obstacles were still identified, including students’ low self-confidence and limited learning media used in the classroom. This study also proposes the integration of collaborative educational technology such as Canva Edu and Google Classroom as innovative solutions to improve interaction quality in discussion-based learning.